2012
DOI: 10.1111/j.1365-2621.2012.03194.x
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of grain tef [Eragrostis tef (Zucc.) Trotter] flour substitution with flaxseed on quality and functionality of injera

Abstract: Summary Injera from tef substituted with two flaxseed forms at 3%, 6% and 9% and control injera showed substitution had a significant effect on injera proximate, energy, titratable acidity (TA), total phenolics (TP) contents and sensory acceptability. Flaxseed forms had influence on moisture, fibre, total carbohydrate (TC) and TA. With 9% flour and whole flaxseed substitution, percentage energy, moisture, ash, crude protein, fibre and TA increase were 3.5, 27.3, 25.9, 20.4, 114.3 and 10.1, respectively. TC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…As reported by Abebe et al (2007), red teff is superior in iron and calcium content. Girma, Bultosa, and Bussa (2013) also indicated that red teff has high-iron content (36.2 mg/100 g), low TA B L E 3 Antinutritional factors in prepared porridge from RTF, MSF, and PFP fruit powder and individual flours zinc (1.50 mg/100 g), and calcium (66.6 mg/100 g) contents. Higher mineral content (iron, calcium, and zinc) in this study found in porridges prepared from different formulations is due to higher concentration of calcium and zinc in the MSF and iron in RTF.…”
Section: Mineral Contents (Iron Calcium and Zinc)mentioning
confidence: 99%
“…As reported by Abebe et al (2007), red teff is superior in iron and calcium content. Girma, Bultosa, and Bussa (2013) also indicated that red teff has high-iron content (36.2 mg/100 g), low TA B L E 3 Antinutritional factors in prepared porridge from RTF, MSF, and PFP fruit powder and individual flours zinc (1.50 mg/100 g), and calcium (66.6 mg/100 g) contents. Higher mineral content (iron, calcium, and zinc) in this study found in porridges prepared from different formulations is due to higher concentration of calcium and zinc in the MSF and iron in RTF.…”
Section: Mineral Contents (Iron Calcium and Zinc)mentioning
confidence: 99%
“…Upon cooking, a distinct outer layer can be observed, resulting from protein denaturation and starch gelatinisation. Thus, the results clearly showed that teff and oat flour can be used to produce gluten-free pasta of acceptable texture [37] The effect of grain teff flour substitution with flaxseed on quality and functionality of injera was analyzed by Girma, Bultosa, and Bussa, [41]. Injera from teff was substituted with two flaxseed forms at 3%, 6% and 9% and control injera showed substitution had a significant effect on injera proximate, energy, titratable acidity (TA), total phenolics (TP) contents and sensory acceptability.…”
Section: Cookiesmentioning
confidence: 99%
“…Conversely, flavonols presented an extensive decrease (62-82%) after treatment Morales et al (2015) carotenoids, among others) (Capriles et al, 2016). Other studies have reflected the potential for the use of hemp seeds (Rado caj et al, 2014), flaxseeds (Girma et al, 2013) and chia seeds (Costantini et al, 2014) in different gluten-free matrices for the enhancement of the antioxidant capacity of the final products without affecting notably the technological parameters assessed. Flours used as ingredients could also be obtained from apple (Morales et al, 2015), apple pomace (Mir et al, 2015) or jambolan .…”
Section: Additives Gluten-free Matrices (%)mentioning
confidence: 99%